Retrospective analytical study of total abdominal hyeterectomy for benign gynaecological conditions - Pathak, Varuna; Singh, Pallavi; Tripathi, Archna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy, which is one of the most common surgeries performed on women, dates back to ancient time. This retrospective study was done to determine a baseline data on various indications for total abdominal hysterectomy for benign gynaecological conditions, most common presenting symptoms, and socio-economic status and their histopathology correlation. Methods: This retrospective study was performed in the department of Obstetrics and gynaecology, in collaboration with Department of Pathology, Gandhi Medical College, Bhopal. Baseline data were collected from inpatient files and histopathology reports to determine the indication for surgery, pattern of gynaecological diseases, and distribution with respect to age, parity, rural, urban, socio-economic status and final histopathology correlation. Histopathology reports were collected from Department of Pathology. Results: Majority of women undergone TAH for benign gynaecological diseases were in age group of 40-49 years [n=341 (48.99% cases)], multi para and from urban areas (57.26%). most common indication for TAH is fibroid uterus [n=347 (49.85%)]. The most common mode of presentation is excessive prolonged frequent bleeding per vagina (58.14%). Most common histopathology reports of TAH were leiomyoma with chronic cervicitis {n=347 (49.78%)}. Conclusions: Majority of women undergoing for TAH for benign gynaecological conditions have great satisfaction as they got relieved from their complaints and very minimum post-operative complications, but their long term outcome are still debatable.